Is palliative care support associated with better quality end-of-life care indicators for patients with advanced cancer? A retrospective cohort study. Issue 1 (31st January 2018) - Ziegler, Lucy E; Craigs, Cheryl L; West, Robert M; Carder, Paul; Hurlow, Adam; Millares-Martin, Pablo; Hall, Geoff; Bennett, Michael I
Abstract : Objectives: This study aimed to establish the association between timing and provision of palliative care (PC) and quality of end-of-life care indicators in a population of patients dying of cancer. Setting: This study uses linked cancer patient data from the National Cancer Registry, the electronic medical record system used in primary care (SystmOne) and the electronic medical record system used within a specialist regional cancer centre. The population resided in a single city in Northern England. Participants: Retrospective data from 2479 adult cancer decedents who died between January 2010 and February 2012 were registered with a primary care provider using the SystmOne electronic health record system, and cancer was certified as a cause of death, were included in the study. Results: Linkage yielded data on 2479 cancer decedents, with 64.5% who received at least one PC event. Decedents who received PC were significantly more likely to die in a hospice (39.4% vs 14.5%, P<0.005) and less likely to die in hospital (23.3% vs 40.1%, P<0.05), and were more likely to receive an opioid (53% vs 25.2%, P<0.001). PC initiated more than 2 weeks before death was associated with avoiding a hospital death (≥2 weeks, P<0.001), more than 4 weeks before death was associated with avoiding emergency hospital admissions and increased access to an opioid (≥4 weeks, P<0.001), and more than 33 weeks before death was associated with avoiding late chemotherapy (≥33 weeks, no chemotherapy P=0.019, chemotherapy over 4 weeks P=0.007). Conclusion: For decedents with advanced cancer, access to PC and longer duration of PC were significantly associated with better end-of-life quality indicators.